An amphiphilic B, O-chelated aza-BODIPY dye: synthesis, pH-sensitivity, and aggregation behaviour in a H2O/DMSO mixed solvent. Issue 27 (23rd June 2021) - Lei, Bin; Pan, Hongfei; Zhang, Yongjie; Ren, Xiang-Kui; Chen, Zhijian
Abstract : A new amphiphilic B, O-chelated aza-BODIPY dye with pH sensitivity and J-type aggregation properties in H2 O/DMSO is reported. Abstract : A novel amphiphilic B, O-chelated azadipyrromethene (aza-BODIPY) dye, containing hydrophobic dodecyloxy groups and hydrophilic tetraethylene glycol (TEG) chains, was synthesized and characterized by NMR, HRMS, Vis/NIR absorption and fluorescence spectroscopy. The B, O-chelated dye 1 exhibited largely bathochromically shifted NIR absorption and fluorescence spectra in comparison with common BF2 -chelated aza-BODIPY dyes. Upon gradual addition of trifluoroacetic acid (TFA) to the dye 1 solution, obvious spectral changes were observed in Vis/NIR absorption and fluorescence spectroscopy measurements. Meanwhile, the colour change of the dye 1 solution from pink to blue was noticeable by the naked eye, indicating the pH-sensitivity of dye 1 . The pH-sensitivity of dye 1 under acidic conditions could be ascribed to the formation of dye species 2·H + . Furthermore, owing to the amphiphilic feature of dye 1, it self-assembled into J-type aggregates in a mixed solvent of water/DMSO (2/8, v/v). Temperature-dependent Vis/NIR spectroscopic studies revealed a cooperative aggregation process of dye 1 and a nanowire-like morphology of the nanoaggregates was observed by AFM.